Penggunaan Analisis SWOT pada Skenario Baru Pengisian Daya untuk Kendaraan Listrik - Bekti Nugrahadi; Nasyita Vivi Amalia; Isna Nugraha; Erna Indriastiningsih (Program Studi Teknik Industri Universitas Setia Budi, 2023)
The number of electric vehicles in Indonesia is currently increasing. One of the problems that hinder the development of electric vehicles is the long charging time. Various ways have been done to overcome the problem of long charging times, including swapping batteries, but this is still not applicable to all types of electric vehicles in Indonesia. Electric vehicle charging facilities in Indonesia are still limited, so there is a need for a good business strategy to minimize queues and uncertainty in waiting times by customers. This study discusses the business schemes of several ways of charging electric vehicles in Indonesia and examines the advantages and disadvantages of each business scheme using SWOT analysis. The strategy in the SWOT analysis focuses on increasing promotion and education to the public, increasing services and the number of charging station locations, setting competitive prices, and expanding partnerships.